Conservative mechanism through various rapeseed (Brassica napus L.) varieties respond to heavy metal (Cadmium, Lead, Arsenic) stress - Li, Lingyu; Fan, Zhanhuang; Gan, Qingqin; Xiao, Gang; Luan, Mingbao; Zhu, Rilong; Zhang, Zhenqian (Frontiers in Plant Science, 2025)
IntroductionHeavy metal soil pollution is a global issue that can be efficiently tackled through the process of phytoremediation. The use of rapeseed in the phytoremediation of heavy metal-contaminated agricultural land shows great potential. Nevertheless, its ability to tolerate heavy metal stress at the molecular level remains unclear.MethodsHere, with 7-day seedlings as raw materials, we investigated physiological and biochemical indexes, analyzed the transcriptome sequencing for different treated materials (control, 50×, and 100×), combined with the results of transcriptome and proteome sequencing of the near-isogenic lines (F338 and F335) to reveal the response mechanism to heavy metal stress. Due to oxidative stress response caused by heavy metal stress, there are heavy effects on the emergence of rapeseeds and the growth of seedlings. Although rapeseed can alleviate oxidative stress by enhancing the enzyme activity, especially peroxidase in the oxidation system, this process has its limits. Rapeseed plants activate antioxidase, transport enzymes, and biological regulation to cope with heavy metal stress. Among these responses, peroxidase, ABC transporters, and abscisic acid are particularly significant in this process.Results and discussionBased on this study, we identified a breeding material with high adsorption capacity for heavy metals, which contributed to the research on resistance breeding in rapeseed. The results of this study may be useful to alleviate heavy metal soil pollution and tackle edible oil shortages in China.